Factors Affecting the Creation of added Value for the Processing of Cinnamon Products of the People in Nambak District, Luang Prabang Province - manhmany, Kongmee; SOMSAMONE, Vilayphone; SIPHADA, Vatthanaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
In this Research aim to study the situation of creating added value by transforming cinnamon into cinnamon products, the factors that affect the creation of added value by transforming cinnamon into cinnamon products and the development direction in creating added value by transforming cinnamon into cinnamon products of the people of Nambak District, Luang Prabang Province. which uses qualitative and quantitative study methods using questionnaires from a sample group of 174 people. Then bring the data to analyze and organize the data in order to find descriptive statistics and reference statistics using SPSS version 22.0 program to analyze the data, the data as a result of the study as follows: 1) The result were situation of creating added value by transforming cinnamon into a cinnamon product. Most of the workers used in the production of cinnamon are family members. Most of the packing and labeling do not have a logo. Cinnamon sticks are different from others because they have sesame seeds or many other products. Raw cinnamon is collected by ourselves. In one year, we can produce enough cinnamon sticks to meet the needs of customers. Cinnamon sticks are not advertised. Most of the production and distribution of cinnamon sticks is in the form of self-production and self-sale, producing more than 11,000 cinnamon sticks per year, the customers who come to buy cinnamon sticks are domestic tourists, the problem of producing cinnamon sticks is that there are no raw materials as needed. 2) Factors that affect the creation of added value for the processing of cinnamon products of the people of Nambak District, Luang Prabang Province, it was found that there are 4 factors that affect the entrepreneurial, capital and the aspect of creating added value with Brand with statistical significance. 3) The way to create added value is to have promotions and provide more information or get back when the customer is not satisfied and to create a brand that is trustworthy, memorable, should have a story and repeated purchases from consumers, should consider raw materials by selecting local raw materials that have a story and a distinctive difference and value, should focus on premium and increased demand so as to produce more cinnamon sticks.